Low carbon oil production: Enhanced oil recovery with CO2 from North Sea residual oil zones. (August 2018) - Stewart, R. Jamie; Johnson, Gareth; Heinemann, Niklas; Wilkinson, Mark; Haszeldine, R. Stuart
Highlights: Hydrodynamically derived Residual Oil Zones (ROZ) exist in the North Sea Basin. CO2 EOR in ROZ can increase oil reserves and produce low carbon intensity oil. CO2 EOR in ROZ can store CO2 and facilitate CO2 storage. Abstract: Residual Oil Zones (ROZ) form when oil has leaked or migrated from a reservoir trap through geological time, leaving a zone of immobile oil. Here we assess the feasibility of ROZ production with CO2 flooding, in a North Sea oil field for the first time. We identify a hydrodynamically produced ROZ, with an oil saturation of 26%, in the Pierce Oil Field of the Central North Sea and adapt established recovery factors for Carbon Dioxide Enhanced Oil Recovery (CO2 EOR) from onshore fields, to estimate oil resource and CO2 storage potential. Our mid case results show that CO2 utilisation increases commercial reserves by 5–20% while storing 15 M t CO2 . Based on our calculations CO2 EOR can produce low carbon intensity crude oil from a mature basin and could store more CO2 than is released from the production, transport, refining and final combustion of oil.